IMPACT OF THE USE OF MOBILE APPLICATIONS AND DIGITAL PLATFORMS IN CARDIOPULMONARY RESUSCITATION: AN INTEGRATIVE REVIEW (REMUNOM, 2025)
INTRODUCTION: Over the years, technology has gained significant space in the healthcare field and, consequently, has boosted creativity with the purpose of innovating the services provided. Mobile applications and digital platforms have stood out by facilitating access to cardiopulmonary resuscitation (CPR).OBJECTIVE: To analyze the impact of mobile applications and digital platforms on the performance of cardiopulmonary resuscitation in individuals with cardiac arrest.METHODS: An Integrative Literature Review was conducted through searches in the Medical Publisher (PUBMED), Virtual Health Library (BVS), and Scientific Electronic Library Online (SCIELO) databases. Health Sciences Descriptors in English were used: Cardiopulmonary Resuscitation, Mobile Applications, and Survival. After applying exclusion criteria, a final sample of 7 articles was obtained.RESULTS: After analyzing the articles, the most prevalent language was English, with the years 2020 and 2025 showing the highest incidence. The most prominent journal was BMC, and the most common study design was the randomized clinical trial. The analysis also revealed that the activation of rescuers through mobile applications is associated with increased survival after out-of-hospital cardiac arrest. The use of these applications also contributes to a higher rate of bystander-initiated CPR.CONCLUSION: Digital technologies enhance CPR but face challenges such as infrastructure and access to AEDs. Public policies that integrate innovation and training are essential to optimize their impact.